Compatibility of Entomopathogenic Nematodes with Chemical Insecticides for the Control of Drosophila suzukii (Diptera: Drosophilidae) - da Costa Dias, Sérgio (2024)
The spotted-wing drosophila, Drosophila suzukii (Matsumura) (Diptera: Drosophilidae), isa pest that reduces the productivity of small fruits. Entomopathogenic nematodes (EPNs) and chemical insecticides can suppress this pest, but the compatibility of the two approaches together requires further examination. This laboratory study evaluated the compatibility of Steinernema brazilense IBCBn 06, S. carpocapsae IBCBn 02, Heterorhabditis amazonensis IBCBn 24, and H. bacteriophora HB with ten chemical insecticides registered for managing D. suzukii pupae. In the first study, most insecticides at the recommended rate did not reduce the viability (% of living infective juveniles (IJs)) of S. braziliense and both Heterorhabditis species. The viability of S. carpocapsae was lowered by exposure to spinetoram, malathion, abamectin, azadirachtin, deltamethrin, lambda-cyhalothrin, malathion, and spinetoram after 48 h. During infectivity bioassays, phosmet was compatible with all the EPNs, causing minimal changes in infectivity (% pupal mortality) and efficiency relative to EPN-only controls, whereas lambda-cyhalothrin generally reduced infectivity of EPNs on D. suzukii pupae themost, with a 53, 75, 57, and 13% reduction in infectivity efficiency among H. bacteriophora, H. amazonensis, S. carpocapsae, and S. brazilense, respectively. The second study compared pupal mortality caused by the two most compatible nematode species and five insecticides in various combinations. Both Heterorhabditis species caused 78–79% mortality among D. suzukii pupae when used alone, and were tested in combination with spinetoram, malathion, azadirachtin, phosmet, or novaluron at a one-quarter rate. Notably, H. bacteriophora caused 79% mortality on D. suzukii pupae when used alone, and 89% mortality when combined with spinetoram, showing an additive effect. Novaluron drastically reduced the number of progeny IJs when combined with H. amazonensis by 270 IJs andH. bacteriophora by 218. Any adult flies that emerged from EPN–insecticide-treated pupae had ashorter lifespan than from untreated pupae. The combined use of Heterorhabditis and compatiblechemical insecticides was promising, except for novaluron.